2019
DOI: 10.9758/cpn.2019.17.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Self-referential Processing and Their Clinical Implications in Social Anxiety Disorder

Abstract: Social anxiety disorder (SAD) is associated with aberrant self-referential processing (SRP) such as increased self-focused attention. Aberrant SRP is one of the core features of SAD and is also related to therapeutic interventions. Understanding of the underlying neural correlates of SRP in SAD is important for identifying specific brain regions as treatment targets. We reviewed functional magnetic resonance imaging (fMRI) studies to clarify the neural correlates of SRP and their clinical implications for SAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 114 publications
1
18
0
Order By: Relevance
“…As mentioned, it is anticorrelated with task‐positive networks and interacts with other brain networks to perform top‐down emotion regulation 48 . Thus, a disrupted DMN connectivity, as we found in PD‐ANX compared to PD‐no‐ANX patients, may interfere with emotions regulation and introspective processes, both features related to anxiety disorders 49,50 . Indeed, DMN changes have been detected in patients with anxiety, 16,51‐53 with a clinical correlation with symptom severity 16 …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…As mentioned, it is anticorrelated with task‐positive networks and interacts with other brain networks to perform top‐down emotion regulation 48 . Thus, a disrupted DMN connectivity, as we found in PD‐ANX compared to PD‐no‐ANX patients, may interfere with emotions regulation and introspective processes, both features related to anxiety disorders 49,50 . Indeed, DMN changes have been detected in patients with anxiety, 16,51‐53 with a clinical correlation with symptom severity 16 …”
Section: Discussionmentioning
confidence: 52%
“…48 Thus, a disrupted DMN connectivity, as we found in PD-ANX compared to PDno-ANX patients, may interfere with emotions regulation and introspective processes, both features related to anxiety disorders. 49,50 Indeed, DMN changes have been detected in patients with anxiety, 16,[51][52][53] with a clinical correlation with symptom severity. 16 An intrinsic abnormal functional connectivity within the DMN has been also associated with cognitive processing in several neurodegenerative disorders, including PD, with and without cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…An elaborate cognitive–behavioral model proposed that pathological self-referential processing is an important factor in the developing and continuing to experience social anxiety disorder [ 5 ]. Increased activity in cortical midline structures (eg, medial prefrontal cortex, posterior cingulate cortex) and limbic areas (eg, amygdala, anterior cingulate cortex, insula) has been linked to biased self-referential processing [ 5 , 6 ] in social anxiety disorder. Altered activation in these brain areas is also correlated with abnormal self-focused attention [ 7 ], which includes socially anxious individuals’ fear of being evaluated [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was revealed that healthy participants who exhibited greater DMN region activity during mindfulness meditation reported greater state anxiety 81 . In individuals with anxiety, abnormal hyperactivation of the DMN may result from hypersensitivity to salient self-relevant stimuli and higher post-event rumination 82 .…”
Section: Discussionmentioning
confidence: 99%